Importance of early diagnostics of chronic obstructive pulmonary disease in patients with coronary heart disease - A. N. Kuznetsov; N. Yu. Grigoryeva; E. G. Sharabrinv (Кардиоваскулярная терапия и профилактика)
Aim. To study the specific clinical features in patients with coronary heart disease, CHD (stable effort angina, SEA) and chronic obstructive pulmonary disease (COPD), in order to improve early diagnostics of this combined pathology. Material and methods. The study was a retrospective analysis of 958 medical histories. Co-existing COPD was registered in 251 patients (26,3 %). Therefore, Group I included 251 patients with SEA and COPD (26,3 %), while Group II included 707 SEA patients without COPD (73,7 %). Results. In Group I, there were more men than women, by 5,7 % (р<0,05). No significant differences in age and angina functional class were observed between Groups I and II. In patients with SEA and COPD, the prevalence of arterial hypertension and myocardial infarction was higher than in Group II (р<0,05). In addition, Group I was characterised by higher prevalence of dyspnoea, palpitation, C-reactive protein elevation, and lipid metabolism disturbances. Conclusion. Among chronic CHD patients hospitalized to the cardiology unit, co-existing COPD was registered in 26,3 %. The combination with COPD aggravated the clinical course of CHD. The study results support the use of lung function assessment in smoking CHD patients, to diagnose co-existing COPD.